2018
DOI: 10.1038/s41467-018-03065-7
|View full text |Cite
|
Sign up to set email alerts
|

Absence of warmth permits epigenetic memory of winter in Arabidopsis

Abstract: Plants integrate widely fluctuating temperatures to monitor seasonal progression. Here, we investigate the temperature signals in field conditions that result in vernalisation, the mechanism by which flowering is aligned with spring. We find that multiple, distinct aspects of the temperature profile contribute to vernalisation. In autumn, transient cold temperatures promote transcriptional shutdown of Arabidopsis FLOWERING LOCUS C (FLC), independently of factors conferring epigenetic memory. As winter continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(144 citation statements)
references
References 48 publications
12
127
0
3
Order By: Relevance
“…However, Arabidopsis accessions are known to use the spectral quality of ambient light to differentiate the proximity of kin versus nonkin (Crepy & Casal, 2015), resulting in phenotype matching among kin (Till-Bottraud & de Villemereuil, 2015). This lends support to our hypothesis that S NIL acceleration is due to phytochrome-mediated shade avoid- (Angel et al, 2015;Burghardt et al, 2016;Duncan et al, 2015;Hepworth et al, 2018;Shindo, Lister, Crevillen, Nordborg, & Dean, 2006). On the other hand, increased temperature in the summer accelerated reproduction, likely mediated by FLM response to high ambient temperature (Lutzet al, 2017(Lutzet al, , 2015Sureshkumar et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, Arabidopsis accessions are known to use the spectral quality of ambient light to differentiate the proximity of kin versus nonkin (Crepy & Casal, 2015), resulting in phenotype matching among kin (Till-Bottraud & de Villemereuil, 2015). This lends support to our hypothesis that S NIL acceleration is due to phytochrome-mediated shade avoid- (Angel et al, 2015;Burghardt et al, 2016;Duncan et al, 2015;Hepworth et al, 2018;Shindo, Lister, Crevillen, Nordborg, & Dean, 2006). On the other hand, increased temperature in the summer accelerated reproduction, likely mediated by FLM response to high ambient temperature (Lutzet al, 2017(Lutzet al, , 2015Sureshkumar et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
“…The winter annual S NIL switched between two plastic responses to climate warming based on season: delay in the fall and acceleration in the summer. Its future‐fall delay may have been caused by the attenuation of the vernalization signal present in the fall‐modern simulation (Angel et al, ; Burghardt et al, ; Duncan et al, ; Hepworth et al, ; Shindo, Lister, Crevillen, Nordborg, & Dean, ). On the other hand, increased temperature in the summer accelerated reproduction, likely mediated by FLM response to high ambient temperature (Lutzet al, ; Sureshkumar et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(), who conducted a 2‐year census of the transcript levels of this well‐known temperature‐dependent flowering time gene to uncover the mechanisms by which environmental factors regulate flowering (Figure ). This ground‐breaking study has since been followed up by others in which FLC transcript levels and chromatin states were measured in different localities and field conditions (Nishio et al ., ; Hepworth et al ., ), which increasingly provided a clearer account of the complexity and relevance of the environment for FLC ‐mediated responses.…”
Section: From Lab To the Field: Plant Genomics And Systems Biology Imentioning
confidence: 99%
“…This approach has also been proposed in attempts to engineer crop traits starting from genetics or from genomes (Welch et al , 2005; Yin and Struik, 2008, 2010; Parent and Tardieu, 2014; Wu et al , 2016; Chenu et al , 2018), where simpler models have demonstrated both the potential of crop modelling in general and the significant demands of detailed models for empirical data that varies in availability (Hammer et al , 2006; Asseng et al , 2013). For microorganisms, comprehensive models link the metabolic and molecular level with the cellular (Karr et al , 2012) and population growth scales (Weiße et al , 2015), whereas contemporary work in more complex organisms has necessarily focused more narrowly (Buckley and Mott, 2013; Lynch, 2013; Zhu et al , 2013; Klose et al , 2015; Le Novere, 2015; Hepworth et al., 2018).…”
Section: Introductionmentioning
confidence: 99%